If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4y = 5y + 13 Reorder the terms: 6 + -4y = 13 + 5y Solving 6 + -4y = 13 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 6 + -4y + -5y = 13 + 5y + -5y Combine like terms: -4y + -5y = -9y 6 + -9y = 13 + 5y + -5y Combine like terms: 5y + -5y = 0 6 + -9y = 13 + 0 6 + -9y = 13 Add '-6' to each side of the equation. 6 + -6 + -9y = 13 + -6 Combine like terms: 6 + -6 = 0 0 + -9y = 13 + -6 -9y = 13 + -6 Combine like terms: 13 + -6 = 7 -9y = 7 Divide each side by '-9'. y = -0.7777777778 Simplifying y = -0.7777777778
| 8x^2+43x+15= | | 79.50-45= | | 8x^3+4x^2=0 | | x+(x-12)=208 | | 455+4x=25x | | 4a=7a | | x^3+7x^2+10x-120=0 | | 2x+0y=-6 | | 2-5[h+3]=-28 | | (2c)i+1=-d+6-i | | 24w+48= | | 2(3x+5)=4x+8 | | 2x^2-58x+159=0 | | 1-17=5 | | 3x-2*y=6 | | 25y-4x=455 | | -1.4d=.07 | | y+3=lx-5l | | 5n^2+2n+24=0 | | z=.35 | | b(x)=35.00-0.25x | | 2x+2=8x-52 | | V-14=-5 | | 5x-(-8x)=-26 | | y=-x(-4) | | X-4=3x+36 | | (3)(x)=10-2x | | -8x-25=3x | | 2x+3(x+4)=9 | | 17-9y=-13+16y | | (8y-x^2y)dy+(x+xy^2)dx=0 | | 1.5-0.04x=-3.34 |